Menelusuri Jejak Marginalisasi Anak Disleksia dalam Pendidikan Islam - Afif Syaiful Mahmudin (Medina-te : Jurnal Studi Islam, 2021)
Dyslexic children are part of children who have learning difficulties.In their lives, these children tend to get different treatments. This treatment is ultimately detrimentalto the sufferer. Nevertheles the information of this treatment is not a very short process, but for a long time. This study aims to explain the process of forming marginalization of children with dyslexia. This study begins with observation of dyslexic children who are often underestimated in the academic field. Based on this case, the author tried to explain the results of this study of the child’s environment and relate it to the relevant theory. It aims to make it clearer how the marginalization process was formed. This children do not have physical abnormalities, so they are believed to be able to attend public schools. This reason is what puts the child in public school. After attending school for a while, the development of reading and writing was fairly slow. This condition is exacerbated when the teacher does not understand the type of learning difficulties, so labeling “stupid” is not a new thing to say. Even when carrying out daily tests, almost all of their values are not in accordance with specified standards. Punishment is often obtained. This lack of support is what causes children’s achievement to decline. Inferior is one of the effects ofthis. The willingness to communicate with his friends was reduced. Hecontinued, peers were less enthusiastic in getting along with these children. The opportunity to do things like other students will decrease and feel marginalized. Keywords: Dyslexia; learning difficulties; pedagogic; Islam.